Marena a Lesotho: chiefs, politics and culture in Lesotho - Quinlan, Tim (Social Anthropology, 2017)
'What is a chief?' and 'what do chiefs do?' are the two questions which begin this study of political authority in rural Lesotho. These questions are contained within a broader one, 'why do villagers often hold chiefs, individually and generally, in contempt but recoil at the suggestion of dissolution of the chieftainship?' The latter question arose from the author's initial field experiences to become the basis for a study which examines the history of the chieftainship in Lesotho. This history is seen as a dialectical process involving a struggle over, and a struggle for, the chieftainship. The former struggle refers to the interventions of elites in society, namely senior chiefs, colonial government officials and, in more recent times, post-independence governments and foreign aid agencies. The latter struggle refers to the interventions of chiefs and the rural populace. Having outlined different ethnographic descriptions of Lesotho's chieftainship, in order to illustrate the different criteria of authority which were applied in the making of the chieftainship, the study goes on to consider the efforts of different agencies to make the chieftainship in the image they desired. The contradictions within, and between, these interventions are explored as the study moves towards consideration of why rural Basotho still support the chieftainship. This analysis takes the discussion from the colonial context, during which Basutoland and the chieftainship were created, to contemporary regional and local rural contexts, in which the chieftainship exists. The discussion illustrates how chiefs have been personifications of family and society, and how this representation is being challenged amongst the rural populace today. The multiplicity of forces which have shaped the chieftainship are then drawn together in a conclusion which examines the pivotal role of the chieftainship in the creation of a national identity and in the crisis of legitimacy facing the contemporary state in Lesotho. The study is informed by a marxist theoretical perspective, but it is also influenced by the debate on postmodernism in Anthropology. This leads the study to acknowledge the current context of theoretical uncertainty for ethnographic research, and the opportunities this affords for exploration of new perspectives. One result is that the study examines tentatively the role of bio-physical phenomena in the way Basotho have constructed society and nature, and represented this construction in their collective understanding of political authority.